Hate knows no boundaries: online hate in six nations - Reichelmann, Ashley (Deviant behavior, 2021)
This paper examines cross-national commonalities and differences in online hate speech content, exposure, and emotional reaction. Using online surveys from 18 to 25-year-old respondents in six countries, we find a majority of respondents were exposed to online hate in the preceding 3 months. Commonalities across countries are the platform where the respondents were exposed and how they arrived at such content. Unique national cultures of hate speech also exist, including the common targets and respondents’ emotional reactions. A majority of respondents report feeling angry, sad, or ashamed, but most worrisome may be the substantial numbers who report feelings of hatred or pride after seeing online hate. Given the potential for repeated exposure and the recent increase in hate crimes in the US. and Europe, this finding should serve as a reminder of the dangers of online hate and its potential link to offline violence.